Children, film and literacy - Parry, Becky (Palgrave Macmillan, 2013)
Children, Film and Literacy explores the role of film in children's lives. The films children engage in provide them with imaginative spaces in which they create, play and perform familiar and unfamiliar, fantasy and everyday narratives and this narrative play is closely connected to identity, literacy and textual practices. Family is key to the encouragement of this social play and, at school, the playground is also an important site for this activity. However, in the literacy classroom, some children encounter a discontinuity between their experiences of narrative at home and those that are valued in school. Through film children develop understandings of the common characteristics of narrative and the particular 'language' of film. This book demonstrates the ways in which children are able to express and develop distinct and complex understandings of narrative, that is to say, where they can draw on their own experiences (including those in a moving image form). Children whose primary experiences of narrative are moving images face particular challenges when their experiences are not given opportunities for expression in the classroom, and this has urgent implications for the teaching of literacy.